Analisis Kata Kunci untuk Mendapatkan Konversi Tertinggi dari Platform Google dan Tokopedia - Dimas Pratama Jati; Aris Wahyu Murdiyanto; Kharisma; Nurul Fatimah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2021)
The business world is very closely related to advertising, advertisements in print, electronic and digital media, In advertising on digital media we need keywords as a reference for search engines to find what we want, Targeting the right keywords in articles is very important to help websites easy to find in search engines. However, in choosing these keywords it is often not appropriate or not in accordance with what is desired, where the inaccuracy of the keywords will make the ad not suitable for the site or product being marketed, so that it is not optimal. The first step is to determine the items to be advertised and then look for the right keywords by looking at the Click Through Rate (CTR), which is the ratio of the number of clicks to the number of impressions, then running ads based on the keywords that have been obtained for an item, then analyze the results of running ads. The results of the two platforms between Google Ads and Tokopedia get an increase of visits after running ads, running ads using keywords with high CTR is very influential on visits and sales. It was recorded that during the ads run there were 2 sales that entered Tokopedia with a total of 3 items sold. If the purpose of the ad is for Brand Awareness, it is better to use Google ads to run ads, because the number of impressions of Google ads is better, but if the purpose of the ad is to sell then it is better to use Tokopedia because the number of conversions is more than Google ads.